Recurrent infective endocarditis causing heart valve failure: A case report - Victoria McIntyre, BASc Chemical Engineering (2018 candidate); Jagdish Butany, MBBS, MS, FRCPC; Dina Boles, MD; Tiffany Shao, MD (Elsevier, 2017)
Infective endocarditis (IE) is an infection that does not usually respond rapidly to treatment, often because its early symptoms are non-specific. The diseased valves (native or bioprosthetic) may be calcified and the thrombotic vegetations on them typically friable and embolize easily. Left untreated IE leads to damage to the infected valve and to congestive heart failure (CHF). Its treatment usually requires heart valve replacement. Our 69-year-old patient had IE, and underwent aortic valve replacement (AVR) with a bioprosthesis. This case stresses the complications of IE and its tendency to recur in patients with bioprosthetic heart valves (BHV) who previously had IE. Keywords: Infective endocarditis, Bioprosthetic heart valves, Heart valve, Bioprostheses, Pannus, Vegetation, EPIC® valve